2020
DOI: 10.1038/s41598-020-72726-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of varied combinatorial mixture of non-fishmeal ingredients on growth, metabolism, immunity and gut microbiota of Lates calcarifer (Bloch, 1790) fry

Abstract: The search for suitable fish meal replacements in aqua-diets is a salient agenda in the constant effort of making aquaculture practices more sustainable. In this study, we tested four customised diets composed by systematic inclusion of pre-selected fish meal substitutes, lupin kernel meal, BSF meal, TH and PBM on growth, metabolism, cytokine profile, gut morphology and microbiota of juvenile Lates calcarifer. Five isoproteic and isoenergetic diets were prepared viz. FM100 as a control (without fish meal subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 67 publications
3
23
0
Order By: Relevance
“…Image recognition technology is the one that processes and analyzes medical images using computer technology to identify and extract specific regions and targets [ 12 ]. The research goal is to classify the objects in the images based on the observed images and make judgments, that is, simulate the human cognition and understanding process using a computer [ 13 , 14 ]. A general image recognition system is mainly composed of image segmentation, image feature extraction, and classifier recognition and classification [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Image recognition technology is the one that processes and analyzes medical images using computer technology to identify and extract specific regions and targets [ 12 ]. The research goal is to classify the objects in the images based on the observed images and make judgments, that is, simulate the human cognition and understanding process using a computer [ 13 , 14 ]. A general image recognition system is mainly composed of image segmentation, image feature extraction, and classifier recognition and classification [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, no histopathological changes were observed in these organs in fish fed FPH-supplemented diets indicating that the bioactive properties in FPH might have improved LM diets by reducing the antinutritional factors that protect these tissues from deviation. The ameliorative effects of FPH supplementation in feeds containing alternate protein sources have been reported elsewhere (Chaklader et al, 2020;Egerton et al, 2020;Gupta et al, 2020). Irrespective of FPH supplementation, fermentation might have played a role in improving the quality of LM diets.…”
Section: Discussionmentioning
confidence: 73%
“…Irrespective of FPH supplementation, fermentation might have played a role in improving the quality of LM diets. Gupta et al (2020) found that fish fed fermented lupin diets had no observable negative effects in liver health of barramundi at 75% replacement of FM and FPH supplementation.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…This requires nutritional fortification. 98 Blending insect meal or oil with other materials 96,[99][100][101] or compensating for deficient components in insect-based diets, for example amino acids, 84,102,103 essential FAs from microalgae and supplementing digestive enzymes 65 could allow the inclusion of higher proportions of insect ingredients, thus reducing dependence on marine fish resources.…”
Section: Economic Fish-in Fish-outmentioning
confidence: 99%